The Dynamics of Indonesian Migrant Workers: Their Short- and Long-Term Impact - Santoso, Edy; Kusuwardhani, Vebry Eka; Muslihatinningsih, Fivien (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study integrates factors influencing Indonesian migrant workers into a Panel VECM model that captures both short- and long-term dynamics. Research Objectives: This study investigates the factors that affect the short- and long-term migration of Indonesian migrant workers. Research Methods: This study uses the Vector Error Correction Model (VECM) approach. Panel data were analyzed for six provinces on Java Island, covering the period 2008 to 2023. Empirical Results: This study found significant positive effects of provincial minimum wage, employment opportunity rates, and poverty levels on the short-term migration of Indonesian migrant workers in Java. In the long term, all variables positively influenced Indonesian migrant worker migration, except for poverty, which had a non-significant effect. Implications: These findings indicate an anomaly in the factors influencing the PMI. Therefore, we assert that policymakers in Indonesia must periodically review and adjust the UMP and implement effective price-control measures to ensure that workers’ basic needs are met at a reasonable cost of living. JEL Classification: C33, F22, I32, J61, J62